Occurrence of sibling species of Lutzomyia longipalpis (Diptera : Psychodidae) in Venezuela: First evidence from reproductively isolated sympatric populations - Lampo, M.; Torgerson, D.; Marquez, L. M.; Rinaldi, M.; Garcia, C. Z.; Arab, A. (Amer Soc Trop Med & Hygiene, 1999)
The delimitation of cryptic species within the main vector of the American visceral leishmaniasis, Lutzomyia longipalpis, remains a topic of controversy. An analysis of generic variability based on 8 enzymatic loci revealed fixed differences in 2 diagnostic loci, adenylate kinase (Ak) and hexokinase (Hk), between sympatric and allopatric populations at 4 localities in Venezuela. The absence of heterozygotes for these 2 loci within 1 locality indicates, for the first time, the presence of 2 sympatric reproductively isolated populations or cryptic species within L. longipalpis. Significant differences were also detected between these cryptic species in the allele frequencies of glucose-6-phosphate isomerase (Gpi) and malate dehydrogenase, decarboxylating (Me). One species showed mean heterozygosities that ranged between 6.6% and 6.7%, with 1.6-1.9 alleles detected per locus, while the other had mean heterozygosities that ranged from 4.3% to 6.3%, with 1.3-1.6 alleles per locus. Comparisons of isozyme profiles with published data suggests that 1 species is similar to the L. longipalpis described in Colombian and Brazilian populations, whereas the other has not been previously reported.